Collated Studies on Rectifying Circuit on Impact-Based Piezoelectric Energy Harvesting - Ahmad Nawir, Nur Amalina; Basari, Amat Amir; Xue Yan, Ng (Journal of Telecommunication, Electronic and Computer Engineering (JTEC), 2018)
Nowadays, energy consumption for ultra-low power energy such as piezoelectric energy harvester has suffered a very huge power loss when rectifying the generated AC signal into regulated DC voltage. This paper presents a method on enhancing the efficiency of the proposed rectifier circuit on Lead Zirconate Titanate (PZT) piezoelectric disk. The experiment was conducted by actuating the transducer by applying one single impact pulse only from a weight-drop test setup. The aim of this study is to increase the efficiency of the extracted output power from piezoelectric by reducing the power losses during the rectification process. Enhancements were made by identifying factors affecting the generated output power from the transducer. Four different types of rectifier topologies were studied and optimized by varying the level of forward voltage drop, Vf across the diode. The enhancement of the generated output voltage from the harvester was also conducted by altering and specifically designed the mechanical configuration of the disk’s supporting base in order to increase the displacement of the piezoelectric strain. The system performances have been analyzed and the resulted data have been plotted into voltage and power curves against the resistive impedance. It was found that the power efficiency of full-wave bridge rectifier constructed with the lowest Vf, is the highest compared to the half-wave and the specialized voltage doubler rectifier.